GLOBECOM 2017 - 2017 IEEE Global Communications Conference 2017
DOI: 10.1109/glocom.2017.8254804
|View full text |Cite
|
Sign up to set email alerts
|

Reducing self-interference in full duplex transmission by interference exploitation

Abstract: In this paper, we consider the power minimization problem in a multiuser full-duplex communication system by employing a multi-objective optimization problem via the weighted Tchebycheff method. We propose to exploit the multiuser interference by using the knowledge of the data symbols and channel state information at the full-duplex base station. Simulation results show that significant power savings can be obtained, which leads to substantial reduction of the selfinterference power in the full-duplex systems. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…CI exploitation can also be applied to FD communications for additional performance improvements, as recently studied in [101]- [103] for both PSK and QAM constellations. The CIbased PM problem in a multi-user FD system is considered in [101] and [102], where a multi-objective optimization via the weighted Chebycheff method is employed to study the tradeoff between the two desirable design objectives, which are the total downlink transmit power at the BS and the total uplink power from the UEs. When PSK constellations are considered, the corresponding CI-based optimization for FD communications can be formulated as [102] P PSK CI-FD : min…”
Section: Full-duplex (Fd) Communicationsmentioning
confidence: 99%
“…CI exploitation can also be applied to FD communications for additional performance improvements, as recently studied in [101]- [103] for both PSK and QAM constellations. The CIbased PM problem in a multi-user FD system is considered in [101] and [102], where a multi-objective optimization via the weighted Chebycheff method is employed to study the tradeoff between the two desirable design objectives, which are the total downlink transmit power at the BS and the total uplink power from the UEs. When PSK constellations are considered, the corresponding CI-based optimization for FD communications can be formulated as [102] P PSK CI-FD : min…”
Section: Full-duplex (Fd) Communicationsmentioning
confidence: 99%
“…where (10) is convex and can be solved by standard convex solvers. Please note that, the formulation in (10) is a relaxed form of (9) where the rank one constraint on W i has been dropped. If the resulting solution W i after solving (10) is rank one, the optimal w i can be obtained by applying eigenvalue-decomposition (EVD), otherwise, ramdomization technique [28] can be used to retrieve w i .…”
Section: A Trade-off Optimization Based On Interference Suppressionmentioning
confidence: 99%
“…The spectral and energy efficiency maximization problems in a FD massive multple-input multiple-output (MIMO) relay system were studied in [8]. In contrast to the above works, which are all based on the concept of the traditional interference suppression, where, multi-user interference (MUI) is treated as unwanted, a multi-user FD system was studied in [9]- [11] by exploiting the downlink MUI rather than suppressing it. In [11], it was shown that by exploiting the downlink MUI, the downlink transmit power is reduced significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [? ], [4], [5], the authors used the knowledge of the DL signals at the FD BS to exploit multi-user interference (MUI) instead treating the MUI as unwanted as in traditional interference suppression techniques. In addition, it was shown that by exploiting the downlink MUI, the downlink transmit power is reduced significantly, although the downlink MUI is exploited, the power gains extend to the uplink through the self-interference serving as the link [4].…”
Section: Introductionmentioning
confidence: 99%